Role of corneal biomechanical properties in predicting of speed of myopic progression in children wearing orthokeratology lenses or single-vision spectacles. Issue 1 (27th December 2018) - Wan, Kin; Cheung, Sin Wan; Wolffsohn, James S; Orr, Janis B; Cho, Pauline
Abstract : Objective: To determine the characteristics of children who were likely to progress rapidly and gain the greatest benefit from orthokeratology (ortho-k) treatment. Methods and analysis: The files of 113 children who participated in two myopia control studies and wore either ortho-k lenses (n=62) or single-vision spectacles (SVS) (n=51) were reviewed. Baseline cycloplegic subjective refraction, central corneal thickness, axial length, keratometry, intraocular pressure, corneal biomechanical properties and 24-month axial length data were retrieved and analysed. Results: Multivariate analysis showed that there was significant negative correlation between axial elongation and baseline age and corneal hysteresis (p<0.05) in the SVS group. In the ortho-k group, only baseline age was significantly and negatively associated with axial elongation (p<0.01). Conclusion: Corneal biomechanical properties and baseline age can predict the rate of axial elongation in myopic children. It may be beneficial for younger myopic children with low corneal hysteresis to commence ortho-k treatment as early as possible.